Dosimetric Analysis of Organs at Risk and its Correlation with Radiation Techniques in Left-Sided Breast Radiotherapy (Journal of Analytical Oncology, 2025)
Background: Breast cancer (BC) burden has increased drastically and has been ranked 2nd worldwide and most common in India, with an incidence of 13.5% of all newly diagnosed cancers. Surgery is the main modality of treatment. The aim of adjuvant radiation therapy is to reduce local recurrence and improve survival. In breast radiotherapy, the proximity of the target to sensitive structures together with the uncertainty introduced by respiratory movement, make this treatment one of the most studied to increase its effectiveness. Various techniques like 3DCRT (Three-Dimensional Conformal Radiation Therapy), IMRT (Intensity Modulated Radiation Therapy) and VMAT (Volumetric Modulated Arc Therapy) are used in RT (Radiation Therapy). Although 3DCRT lowers radiation exposure to normal tissues, it can result in suboptimal dosing of the tumor volume. Conversely, IMRT and VMAT achieve better tumor dose coverage but pose greater challenges in protecting organs at risk (OARs). Objectives: This retrospective study aims to highlight the Dosimetric study of OARS, and compare Dosimetric values of different RT Techniques in patients receiving left-sided breast irradiation.Methods: A total of 142 left breast carcinoma patients receiving either whole-breast irradiation or chest wall irradiation were enrolled in this study. The Dosimetric parameters of the heart, left lung and right breast were evaluated and compared, and possible correlations were studied. Results: Of the 142 patients assessed, 62 patients were stage III, 93 patients underwent post-mastectomy radiotherapy and 49 patients with Whole Breast Radiotherapy (WBRT). Majority of patients were treated by 3DCRT technique. Patients were planned for the 50 Gy in 25 fractions (n-72) and 40 Gy in 15 fractions (n-70) radiation dose regimens. Heart mean dose in 3DCRT, IMRT and VMAT is 6, 7.8 and 7.1Gy respectively (p-0.002).On comparing V20 (Volume of lung receiving 20Gy) of ipsilateral (I/L) Lung with 3DCRT, IMRT and VMAT (p-0.998) is 24.8%, 27.5 % and 22.5% respectively. Contralateral (C/L) breast mean dose in 3DCRT was 0.8Gy whereas 5.3Gy and 4Gy respectively in IMRT and VMAT which was statistically significant (p-0.05)Conclusion: Significant correlations for dosimetric parameters were registered between the OARs and RT Techniques. Our results suggest that heart mean dose and C/L breast dose is minimal in 3DCRT compared to IMRT and VMAT techniques.